Beaumaris Castle - Master James of St. George
Beaumaris Castle was built on flat ground, and therefore was given an additional outer wall, or list wall, which surrounded the whole and was flanked by the moat. There were smaller protective towers and enclosures for archers (open from the space between the two walls), with a walkway at the top.